COMPARATIVE EFFICACY OF CONVENTIONAL STABILIZERS IN IMPROVING ENGINEERING BEHAVIOR OF EXPANSIVE SUBGRADES (Jurnal Teknologi (Sciences & Engineering), 2025)
This paper addresses the critical issue of distress in flexible pavements built on expansive Black Cotton soil, where seasonal moisture variations lead to swelling and shrinking, posing a serious threat to durability. Despite extensive research utilizing conventional stabilizers such as cement, lime, and fly ash, the comparative effectiveness of these stabilizers remains uncertain. This study employs a comprehensive approach, integrating conventional tests and microanalysis techniques to assess the engineering behavior of stabilized expansive soil samples. The investigation includes tests like Unconfined Compressive Strength (UCS) for strength evaluation, Free Swelling Index (FSI) for swelling potential estimation, and Atterberg’s limits for evaluating plasticity properties. Additionally, Environmental Scanning Electron Microscope (ESEM) microanalysis is employed to examine the morphology of uncured-unstabilized expansive soil samples and those stabilized with cement, lime, and fly ash after a 28-day curing period. Results indicate that cement emerges as the most effective stabilizer, significantly reducing swelling by up to 42% and increasing strength post-curing by a remarkable fivefold compared to unstabilized-uncured expansive soil. Lime demonstrates exceptional efficacy in reducing plasticity, diminishing Liquid Limit (LL) and Plasticity Index (PI) by 30% and 79%, respectively. In contrast, fly ash is identified as least effective stabilizer, displaying the lowest efficacy in reducing swelling, plasticity, and enhancing strength. Furthermore, the study extends its analysis to evaluate the impact of these stabilizers on rutting and fatigue life of pavements through Finite Element Analysis (FEA) using PLAXIS. The findings contribute valuable insights for practitioners and researchers seeking optimal stabilizer selection for expansive soil-based pavement projects.